Penanggulangan Tindak Pidana Kepemilikan Dan Penggunaan Senjata Api Tanpa Izin Dalam Sistem Peradilan Pidana - Evan Munandar; Suhaimi Suhaimi; Muhammad Adli (Syiah Kuala Law Journal, 2018)
Pasal 1 ayat (1) dan ayat (2) Undang-Undang Darurat Nomor 12 Tahun 1951, menyatakan bahwa “Barang siapa, yang tanpa hak memasukkan ke Indonesia membuat, menerima, mencoba memperoleh, menyerahkan atau mencoba menyerahkan, menguasai, membawa, mempunyai persediaan padanya atau mempunyai dalam miliknya, menyimpan, mengangkut, menyembunyikan, mempergunakan, atau mengeluarkan dari Indonesia sesuatu senjata api, amunisi atau sesuatu bahan peledak, dihukum dengan hukuman mati atau hukuman penjara seumur hidup atau hukuman penjara sementara setinggi-tingginya dua puluh tahun. Namun pada kenyataannya di Wilayah Hukum Pengadilan Negeri Jantho masih terjadi tindak pidana penggunaan senjata api tanpa izin. Penelitian ini bertujuan untuk menganalisis faktor penyebab terjadinya tindak pidana kepemilikan dan penggunaan senjata api tanpa izin, upaya penanggulangan dan hambatan dalam penanggulangan tindak pidana tersebut. Jenis penelitian hukum dan pendekatan yuridis empiris, dengan teknik pengumpulan data melalui penelitian kepustakaan untuk memperoleh data sekunder dan penelitian lapangan untuk memperoleh data primer. Analisis data dengan metode kualitatif. Berdasarkan hasil penelitian diketahui bahwa faktor penyebab terjadinya tindak pidana kepemilikan dan penggunaan senjata api tanpa izin di wilayah hukum Pengadilan Negeri Jantho karena tujuan membela diri, alat untuk mencari nafkah, melaksanakan tugas sebagai anggota GAM. Upaya penanggulangan dilakukan secara preventif dan represif. Hambatan yang dihadapi kurangnya pengawasan oleh kepolisian maksimal.On the paragraph 1 article 1 and 2 of the emergency legislation no 12 of 1951, it was mentioned that “whoever, without permission producing, accepting, trying to attain, giving, trying to give, controlling, carrying, having, keeping, taking, hiding, using, or taking out the firearm, ammunition, or dynamite in Indonesia will be punished capital punishment, life imprisonment, or twenty years imprisoned punishment”. However, in the reality, in Jantho Jurisdiction region, there are still many of criminal act related to the unauthorized use of firearms. It was caused of the security factor in the living area and the lack of knowledge factor on unauthorized ownership of the firearms. This research aims to describe and analyze the causal factor of the criminal act on the unauthorized firearms in the jurisdiction region of Jantho and the effort made to overcome the criminal act of unauthorized ownership and use of firearm. This research is a type of law research, empirical juridical research, or sociology law research, with the technique of data collection conducted through library research to attain the secondary research and field research to attain the primary data. The technique of data analysis used in this research is qualitative. This method is used to easily to understand the causes observed and to connect the problem discussed. Based on the research result, it was revealed that the causal factor of the criminal act on the unauthorized gun ownership in the law area of Jantho court  are: self-defense factor, earning money, the responsibility as an Aceh Free Movement member, the preparation to did other criminal act. The effort made to overcome the criminal act of unauthorized gun use by regularly giving the law and police raid. The repressive efforts made are by investigating, sue the perpetrators   of criminal act on unauthorized gun use to the court based on the legislation, and deciding the criminal decision to the perpetrators by the judge.